Weed control in herbicide-tolerant sunflower - Godar, Amar S. (Kansas State University, 2009)
Several weed species infest sunflower fields, but herbicidal options for broadleaf weed control are limited. In recent years, imazamox and tribenuron herbicides have been registered for POST use in imidazolinone-tolerant and tribenuron-tolerant sunflowers, respectively. Objectives of this study were to 1) investigate the effects of soil nitrogen level on Palmer amaranth control with imazamox in imidazolinone-tolerant sunflower and 2) evaluate crop response and weed control efficacy of single and sequential applications of tribenuron at two rates and the effectiveness of preemergence herbicides followed by postemergence tribenuron in tribenuron-tolerant sunflower. Greenhouse experiments were conducted in Manhattan, KS and field experiments were conducted near Hays, KS in 2007 and 2008. For the first objective, treatments consisted of a factorial arrangement of three soil nitrogen levels (28, 56, and 84 kg/ha) and two imazamox rates (26 and 35 g ai/ha) in a RCBD. Palmer amaranth growth rate increased with increasing soil nitrogen level. In all experiments, plants grown at the highest soil nitrogen level exceeded the maximum recommended plant height (7.6 cm) by >35% at the time of imazamox application. Generally, imazamox rates did not differ in control effectiveness at the 56 kg/ha soil nitrogen level, but the higher 35 g/ha rate was superior to the lower rate at the 84 kg/ha soil nitrogen level because of greater weed size. For the second objective, tribenuron was applied singly at 9 and 18 g/ha, sequentially in all combinations of those rates, and singly at those rates following PRE herbicide treatments. In general, tribenuron at 18 g/ha applied with methylated seed oil adjuvant before weeds exceeded 10 cm in height provided excellent control of most species with insignificant injury to the crop. The need for supplemental PRE herbicides for weed control in tribenuron-tolerant sunflower depends on weed species present and their size at the time of tribenuron application.
Keywords: Weed control; Tribenuron; Imazamox; Sunflower; Palmer amaranth; Crop injury; Agriculture, Agronomy (0285)